2021
DOI: 10.1111/syen.12506
|View full text |Cite
|
Sign up to set email alerts
|

Integrative phylogenomics reveals a Permian origin of Adephaga beetles

Abstract: Beetles are arguably the most diverse group of animals on Earth with over 400 000 described species. Yet the timing of main diversification events among these insects remains debated. The use of phylogenomic data generated using next‐generation sequencing recently resolved most recalcitrant phylogenetic relationships across Coleoptera. However, limited taxon sampling for some major clades still prevents the use of important fossil calibrations that could provide more accurate estimates of the timing of lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 167 publications
(377 reference statements)
1
20
1
1
Order By: Relevance
“…Since there are no reliable fossil calibrations for the "Gondwana group", we chose to use secondary calibrations from higher-level taxonomic studies of Coleoptera. The recent development of robust dated trees for Coleoptera (e.g., Toussaint et al, 2017a;Zhang et al, 2018;McKenna et al, 2019;Baca et al, 2021) allows the ages of more derived lineages to be constrained with a higher degree of confidence than previously. Zealand .…”
Section: Divergence Time Estimation and Historical Biogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…Since there are no reliable fossil calibrations for the "Gondwana group", we chose to use secondary calibrations from higher-level taxonomic studies of Coleoptera. The recent development of robust dated trees for Coleoptera (e.g., Toussaint et al, 2017a;Zhang et al, 2018;McKenna et al, 2019;Baca et al, 2021) allows the ages of more derived lineages to be constrained with a higher degree of confidence than previously. Zealand .…”
Section: Divergence Time Estimation and Historical Biogeographymentioning
confidence: 99%
“…Since there are no reliable fossil calibrations for the 'Gondwana group', we chose to use secondary calibrations from higher-level taxonomic studies of Coleoptera. The recent development of robust dated trees for Coleoptera (e.g., Baca et al, 2021;McKenna et al, 2019;Toussaint, Bloom, & Short, 2017;Zhang et al, 2018) allows the ages of more derived lineages to be constrained with a higher degree of confidence = 198.75, 13.34). We used different tree (Yule versus birth-death) and clock priors (one clock for all partitions versus one clock for each partition) to test for potential differences in resulting time estimates.…”
Section: Divergence Time Estimation and Historical Biogeographymentioning
confidence: 99%
“…Although the oldest body fossils of tiger beetles are Early Cretaceous in age (Cassola and Werner, 2004; Zhao et al, 2019), some research has suggested that their ancestors existed by the Triassic with possible crown-group members by the Jurassic (Baca et al, 2021; Pearson and Ghorpade, 1989). Overall, due to their fragile exoskeletons, even compared to other beetles (Smith et al, 2006), body fossils are extremely uncommon with only a few other Cenozoic examples known to date, such as in Eocene Baltic and Rovno amber, Quaternary asphalt deposits from the Caucasus region, Trinidad, and California, and Pleistocene late glacial deposits from the UK and North America (Matalin et al, 2021; Nagano et al, 1982; Wiesner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is the responsibility of systematic biologists to assemble the natural system, that is, we need to reliably delimit genus- and tribe-level taxa, to make their ecological and distribution attributes informative. But the short fragments are often unsuitable for the building of deep phylogenies and large genomic datasets need to be used ( McKenna et al, 2019 ; Baca et al, 2021 ). These include transcriptomes, whole genome sequences and anchored hybrid capture datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The applied methods of transcriptome and mtDNA analyses are widely used. The genomic datasets dominate among works focusing on deep relationships (transcriptomes and anchored hybrid capture; Misof et al, 2014 ; Kusy et al, 2019 ; McKenna et al, 2019 ; Baca et al, 2021 ). The mitochondrial markers have been used mainly to study the phylogeny of restricted clades ( Toussaint et al, 2014 ; Sharkey et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%